Interseksi Pendidikan, Budaya, dan Politik dalam Media Wayang Kulit di Indonesia - Jati, Wasisto Raharjo (Balai Pelestarian Kebudayaan Wilayah X, 2023)
This paper aims to analyze instrumentation puppet as a pillar of the New Order. Understanding the puppet in reality not only understood as the art, but also as perspective of seeing political behavior. Analysis of this study use Barthesian perspective namely linguistic and mythology. The results showed that the Banyan and Semar are two key words in viewing power hegemony that runs in the puppet arts. Semar later personified by the figure of Soeharto and banyan understood strong power that rooted in public.